PROGNOSTIC FACTORS OF CARDIAC COMPLICATIONS AFTER ISCHEMIC STROKE (BY THE RESULTS OF PROSPECTIVE STUDY) - V. A. Shandalin; A. V. Fonyakin; L. A. Geraskina; Z. A. Suslina (Кардиоваскулярная терапия и профилактика, 2014)
Aim. To set prognostic factors of cardial complications after ischemic stroke.Material and methods. Into prospective cohort observational study totally 148 patients included with ischemic stroke, at the age of 60 (52;68) y. All patients underwent clinic-instrumental, neurological and cardiological investigations. At the 20th day after stroke all patients underwent 24-hour Holter monitoring with the rhythm and conduction disorders analysis, transient ischemia, temporal and spectral characteristics of the heart rate variability. Duration of prospective study was 35 (28; 40) months. Cardial complications were registered: myocardial infarction (MI), instable angina, acute heart failure (AHF), including the acute decompensation of chronic heart failure leading to hospitalization, sudden cardiac death (SCD) and all cases of cardiac deaths.Results. During the study in 17 (11%) patients, 19 cardiac complications registered: 7 episodes of unstable angina, 4 acute MI, 5 cases of AHF and 3 cases of SCD. In 1 patient consequently registered 2 cardiac complications – unstable angina and MI. In 8 patients there was cardiac death due to MI (n=2), AHF (n=3) and SCD (n=3). The predictors established for cardiac complications after ischemic stroke: age more than 67 y.o., ventricular arrhythmias of higher grades, chronic forms of ischemic heart disease, parameters of five-minute standard deviations of cardiointervals (SDNN) <35 ms, higher frequencies amplitude <43 ms2 and low frequencies <196 ms2.Conclusion. To every patient after ischemic stroke, especially repeated, the cardial status must be thoroughly explored with Holter monitoring to evaluate the grades of ventricular arrhythmias and heart rate variability, which may provide individualized stratification of cardiac complications risk at long-term periods after stroke and more effective planning of the events for secondary cardiovascular prophylaxy.